A novel measuring system enables the noncontact real-time monitoring of very low net concentrations of plant-emitted ions in the air that may serve for plant ion homeostasis research - Toshiro Kawaguchi; Katsuya Mukae; Yoshihiro Takahashi; Hirofumi Ichiki (BMC Plant Biology)
Abstract Background Plants emit into the air trace amounts of cations (e.g., K+ and NH4 +) and anions (e.g., NO3 − and PO4 3−) that are involved in their physiological processes. Background ion charges in the air mask very low concentrations of plant-emitted ions in the air. Conventional air ion counters cannot measure these concentrations. Therefore, we devised a single magnetically levitated electrode ionization chamber (MALIC) unit system incorporating 3 MALIC units—a novel measuring system that is noninjurious to plants by being noncontact and pulsed electronic field-free and allows for the real-time monitoring of very low net concentrations (10–1 to 10 ions/mL) of plant-emitted ions in the air by subtracting background ion charges from cation and anion concentrations. The present study aimed to assess the performance of the system to measure these ion charges and ion and net ion concentrations. Results Concentrations of ions, which had been emitted into the air by two Crassulacean Acid Metabolism plants [Crassula ovata (1 strain; 390 leaves) and Schlumbergera truncata (4 strains; 110 stem nodes per strain)] cultivated under almost the same cultivation conditions (light source, light intensity, light/dark state, flowering/flowerless stage, temperature, and humidity), were measured. Consequently, the system precisely measured very low background ion charge-subtracted, net, and average net concentrations of the relevant concentrations and separately collected cation and anion aggregates. Changes in net and average net ion concentrations in Crassula ovata that were exposed to three light sources (silica light, white fluorescent light, and fluorescent light for plant growth) and in Schlumbergera truncata in the light (white fluorescent light)/dark states and at the flowering/flowerless stages were congruent with their photosynthetic profiles, thus providing indirect evidence for the physiological traits of CAM plants. Conclusion The performance of a single MALIC unit system to precisely measure very low net ion concentrations in the air was demonstrated successfully, thus meeting its objective. The system monitors the concentrations in a real-time manner and separately collects the aggregates of cations and anions emitted from leaves, stem nodes, and flowers, thus directly providing ion aggregate materials as a novel measurement tool for ion homeostasis research without causing any damage to plants.